Performance Comparison between PID And Fuzzy Logic Controller in Position Control System of Dc Servomotor - Md Ghazaly, Mariam (Universiti Teknologi Malaysia, 2006)

(untitled)
The objective of this paper is to compare the time specification performance between conventional controller and artificial intelligence controller in position control system of a DC motor. This will include design and development of a GUI software using Microsoft Visual Basic 6.0 for position control system experiment. The scope of this research is to apply direct digital control technique in position control system. Two types of controller namely PID and fuzzy logic controller will be used to control the output response. An interactive software will be developed to visualize and analyze the system. This project consists of hardware equipment and software design. The hardware parts involve in interfacing MS150 Modular servo System and Data Acquisition System with a personal computer. The software part includes programming real-time software using Microsoft Visual Basic 6.0. Finally, the software will be integrated with hardware to produce a GUI position control system.